Investigation of metal damage by ultrasonic broadband spectroscopy. (March 2019) - Kravcov, A.; Shibaev, I.A.; Sizikov, M.V.; Pavlov, I.A.; Zarubin, V.P.; Arrigoni, M.; Pospichal, V.; Zharinov, A.N.
Abstract: Broadband ultrasonic spectroscopy is used for locating microcracks about 50 μm wide and more. The method allows the depth of occurrence of defects and the length of cracks to be determined with an accuracy of no more than 200 μm and no less than 500 μm, respectively. Metal articles may be up to 20 cm thick with a cross-sectional area of 3 to 10 m 2 .